Familial multiple lipomatosis with clear autosomal dominant inheritance and onset in early adolescence. (18th February 2011) - Lee, Cheng-Hiang; Spence, Roy A J; Upadhyaya, Meena; Morrison, Patrick J
Abstract : Familial multiple lipomatosis is rare. Several modes of inheritance have been proposed but no conclusive evidence shown, although some families have suggested autosomal dominant inheritance. The authors describe a family with multiple lipomatosis showing clear autosomal dominant inheritance, and no mutations within the NF1, SPRED1 or Cowden disease (PTEN) genes. Familial autosomal dominant lipomatosis is a rare but distinct entity.